Benefícios percebidos na implantação de boas práticas de fabricação - Palma, Fernando José Salzarulo (2014)
This work consists on a quantitative research with employees of several companies in the healthcare area, aiming to show the different perceptions of benefits between the participants, related to the implementation of Good Manufacturing Practices, the RDC 16:2013 . We could also note in this work that, depending on the area there were different perceptions of impacts. As can be seen, the maturity of the documents and records in the production area, makes this feel less impact, while other areas have a big difference in benefits perception, and finally, those answers are compared to a, yes or no question, of the implementation of this Standard